Cytogenetic study of neoplastic and nonneoplastic cells of the skin - Pavarino, E. C.; Antonio, JR; Pozzeti, EMD; Larranaga, HJA; Tajara, E. H. (Elsevier B.V., 1995)
We describe the cytogenetic study of six neoplastic and eight nonneoplastic skin samples from sun-exposed body sites or sites close to tumors. The cytogenetic findings revealed that chromosome rearrangements are common in sun-exposed normal skin, similar to the situation in cutaneous tumors, and suggest that such karyotypic abnormalities might be indicative of the genetic instability caused by specific mutations and resulting from carcinogenic exposure of the tissue.